Fermentation strategies for improving the production of bacteriocin-like inhibitory substances by Lactobacillus brevis C23 with nutrient supplementation, pH, and temperature variations - Sreedharan, Dharni Kuhan; Abbasiliasi, Sahar; Mohamed, Mohd Shamzi; Zhang, Jin Ng; Ariff, Arbakariya; Lee, Chee Keong; Joo, Shun Tan (Wiley-Blackwell, 2021)
In this study, fermentation strategies were carried out for improving the production of bacteriocin-like inhibitory substances by Lactobacillus brevis C23 with nutrient supplementation, pH, and temperature variations, as well as fed-batch cultivation. The BLIS activity was highest (91.52%) in the MRS medium supplemented with 1.5% (w/v) lactose and 1% (w/v) meat extract. pH 5 augmented both the cell biomass and BLIS activity, but incubation temperature only affected growth at 37°C. Fed-batch cultivation strategy that utilized meat extract feeding would positively affect cell growth, whereas BLIS activity was enhanced by lactose feeding. The highest BLIS activity from L. brevis C23 was obtained at the 24 hr mark by feeding the culture medium with lactose (77.73%). The BLIS production of L. brevis C23 fed with meat extract followed a similar trend to lactose (74.20%). Increased BLIS activity in the final solution would reduce the downstream step such as concentrating the purified product.